Samkhya Dalam Teks Tattwa Sanghyang Mahajnana - sri marselina wati (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2023)
Samkhya is a very old Hindu philosophy, because both the sruti and smrti scriptures are influenced by this philosophy. Archipelago literary works such as lontar and kakawin also contain a lot of Samkhya philosophy in the concept of Shivaism, this study aims to find out the Samkhya teachings contained in the text Tattwa Sanghyang Mahajnana. This research is classified as a qualitative research because the data is presented descriptively by using data collection methods namely, interviews, literature studies, and observation. The Samkhya philosophy contained in the Tattwa Sanghyang Mahajnana is the evolution of the universe, ways of obtaining truth, and the concept of liberation in the Samkhya in the text of the Tattwa Sanghyang Mahajnana. The evolution of the universe originates from Purusa and Prakerti then tri guna is likened as a child, while intelligence and mind are likened as a plow, and the ten senses are oxen and the base of the heart is likened to rice field in the creation process of samkhya contained in the Tattwa Sanghyang Mahajnanama text which is still based on 25 elements. The process of seeking truth in Samkhya contained in the tattwa sanghyang mahajnana text is, pratyaksa pramana, anumana pramana, and sabda pramana. The concept of liberation in Samkhya contained in the Tattwa Sanghyang Mahajnana text is that humans are free from the causes of dukkha by means of tapa, bratha, yoga, and smadhi by saying the Om syllabel.